Pendampingan Penyusunan Struktur BUMDES Pulotondo Mulyo Berbasis Potensi Ekonomi di Desa Pulotondo, Tulungagung - Fatimah, Annisa; Wijayanti, Rika; Ernawati, Widi Dwi; Magdalena, Marlina; Indrayati, Indrayati (Abdimas Indonesian Journal, 2024)
The Community Service Team (PKM) of the Malang State Polytechnic (Polinema) carried out activities on July 3-4, 2024 at Pulotondo Village, Ngunut District, Tulungagung Regency. This was done to assist the Village-Owned Enterprise or often referred to as Bumdes Pulotondo Mulyo in Pulotondo Village, Ngunut District - Tulungagung Regency in compiling its organizational structure. The existence of Pulotondo village through Bumdes Pulotondo Mulyo must receive serious attention. Bumdes is expected to be able to manage assets, service providers, and other businesses to improve the welfare of its people according to Permendesa No. 4 of 2015. All capital for Bumdes Pulotondo Mulyo is obtained through direct participation from separated Village assets. This PKM activity is carried out in several stages, namely during pre-activity, activity implementation and post-activity. Based on the results of the pre-activity, the potential superior businesses owned by Bumdes are catering businesses, livestock/fishery feed distributors, and have a household waste business management plan. Therefore, the design of the Bumdes Management structure must be appropriate. To achieve organizational goals, Bumdes management really needs the support of management functions. The organizational structure of Bumdes Pulotondo Mulyo is not yet effective and stable. The initial steps that have been taken are to prepare the organizational structure and educate the job descriptions of all Bumdes managers. This activity received a positive perception from the Bumdes Pulotondo Mulyo Management. According to Bumdes, the PKM activity is very useful and opens up new insights that are ready to be applied to the Bumdes organization. It is hoped that this assistance can continue to be focused on strengthening the community's economy, increasing information, knowledge and skills, which must be carried out in multiple aspects, both from the aspects of society, social, culture, village government policies and marketing potential for Bumdes Pulotondo Mulyo.